2012
DOI: 10.1177/230949901202000313
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Short-Term Outcome of Hip Arthroplasty

Abstract: purpose. To review nutritional status and outcome of 90 patients who underwent total hip arthroplasty (THA) or hemiarthroplasty. Methods. Records of 51 women and 39 men aged 26 to 96 (median, 71) years who underwent elective THA (n=48) for osteoarthritis, or trauma-related THA (n=10) or hemiarthroplasty (n=32) for subcapital femoral neck fractures using an uncemented femoral stem were retrospectively reviewed. Patient demographics and intra-and post-operative complications were recorded. Patient co-morbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 27 publications
3
37
0
Order By: Relevance
“…Other complications associated with malnutrition in patients undergoing orthopaedic surgery include postoperative hematoma formation, and renal, cardiovascular, and neurovascular complications [7]. Results of our study are consistent with those of other studies showing an association between low serum albumin and an increase in multiple major perioperative complications [5,12,27,32] To our knowledge, our study is the largest to date evaluating the independent association between low serum albumin and perioperative complications after TKA. We focused specifically on elective primary TKAs and provide a detailed analysis of specific complications which are increased in patients with low serum albumin.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Other complications associated with malnutrition in patients undergoing orthopaedic surgery include postoperative hematoma formation, and renal, cardiovascular, and neurovascular complications [7]. Results of our study are consistent with those of other studies showing an association between low serum albumin and an increase in multiple major perioperative complications [5,12,27,32] To our knowledge, our study is the largest to date evaluating the independent association between low serum albumin and perioperative complications after TKA. We focused specifically on elective primary TKAs and provide a detailed analysis of specific complications which are increased in patients with low serum albumin.…”
Section: Discussionsupporting
confidence: 89%
“…Deep periprosthetic infections (acute and chronic) also have been reported at a higher rate in patients with malnutrition [32]. Some studies have concluded that patients with malnutrition had a longer postoperative length of stay [12,27]. Other complications associated with malnutrition in patients undergoing orthopaedic surgery include postoperative hematoma formation, and renal, cardiovascular, and neurovascular complications [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein and energy malnutrition are common among older adults (1)(2)(3)(4)(5), with malnutrition and risk thereof especially high in hospitalized and institutionalized elderly patients. Two-thirds of older people may be at nutritional risk or malnourished (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds of older people may be at nutritional risk or malnourished (6,7). Over half of hip fracture patients have a poor nutritional status (1,3,4,8). Malnutrition is acknowledged to be under-recognized and undertreated in health care (9).…”
Section: Introductionmentioning
confidence: 99%